Multicriteria approach to choose the best cycling route for cycling in the metropolitan region of Cuiabá-MT (Research, Society and Development, 2023)
This study sought to select the best cycling route in the metropolitan region of Cuiabá-MT, considering the opinions of cyclists. To achieve this objective, the Analytic Hierarchy Process (AHP) method was applied, which is a multicriteria decision analysis model. For data collection, an online form was made available in the groups of cyclists in the studied region. The responses of 15 cyclists who presented Consistency Ratio values ​​lower than 0.1 were selected. The socioeconomic profile of the cyclists was collected, and the following results were obtained; the majority are men, single, aged between 20 and 30 years, with incomplete higher education, monthly income of more than 5 minimum wages and residents in the city of Cuiabá. They pedal alone, are beginners, cycle once a week, covering a distance of less than 20 km, 13.33% have already suffered accidents and 53.33% do not use any safety equipment. The results of this work showed that the main criterion that influenced the choice of routes is safety (0.38), followed by infrastructure (0.28), proximity to home (0.18) and topography (0.16). Regarding the cycling routes, Route 4 (Exit to Chapada/Coxipó do Ouro) was in first place with 0.33, followed by Route 1 (Exit to Rondonópolis) with 0.27, Route 2 (Exit to Santo Antônio do Leverger with 0.21 and, finally, Route 3 (Departure to Cáceres) with 0.19. It is hoped that this study can be used as a reference and be an instrument to aid decision-making in the planning of cycling routes in other regions of the country.